Self‐Doped TiAl Nanoparticle/AlN Metal‐Cermet Solar Selective Absorbing Films. Issue 6 (19th December 2021) - Shi, Jing; Zhao, Runqiang; Ke, Shenglan; Wang, Wanrong; Wang, Chengbing
Abstract: Metal‐cermet solar selective absorber films (SSAFs) with nanoparticles embedded in dielectric matrix have been widely used in the field of solar thermal conversion. A new SSAF of TiAlN is fabricated via magnetron sputtering method. By co‐sputtering Ti and Al targets, TiAl nanoparticles are embedded in AlN matrix to form self‐doped absorber layer. And the outermost rough AlN antireflective layer further enhances the optical properties due to the optical trapping effect, as well as the heating crack extension resistance of the surface. As a result, the as‐grown SSAF displays high absorptance reaching up to 0.92 and low thermal emittance of 0.05. The selective absorption mechanism endowed by synergetic effect of intrinsic absorption and multilayers' interference is discussed. The SSAFs optical property is stable in open‐air up to 650 °C,  indicating their enormous potential for high‐temperature solar selective applications. Abstract : A new solar selective absorber film (SSAF) with self‐assembled TiAl nanoparticles is fabricated via one‐step magnetron sputtering. TiAl nanoparticles are embedded in AlN matrix to form self‐doped absorber layer. The outermost rough AlN anti‐reflective layer further enhances selectivity due to optical trapping effect. The as‐grown SSAF displays high absorptance, low thermal emittance and excellent high‐temperature thermal stability.